MINERALOGY AND GEOCHEMISTRY OF HYDROTHERMAL SEDIMENTS FROM THE SERPENTINITE-HOSTED SALDANHA HYDROTHERMAL FIELD (36°34′N; 33°26′W) AT MAR - Dias Á.S.; Barriga F.J.A.S. (My University, 2006)
The Saldanha hydrothermal field is located at the top of a serpentinized massif (Mount Saldanha, MS) at a non-transform offset (NTO5) along the Mid-Atlantic Ridge (MAR), south of the Azores. It is one of the rare known sites on a worldwide basis where direct evidence of low-temperature (7-9°C) hydrothermal activity has been provided by direct observation of hydrothermal fluid venting through small orifices in the ocean floor sedimentary cover. This study focuses on the mineralogy and geochemistry of 14 sediment cores collected at MS. For comparison, four samples collected at the Rainbow site (NTO6) were also studied. Mount Saldanha hydrothermal sediments are highly "diluted" within a dominant foraminiferal nanofossiliferous ooze with small fragments of underlying rocks. The mineral assemblage of the hydrothermal component is characterized by sulphides, nontronite, smectites, poorly crystallized Mn oxyhydroxides and amorphous material. Cu, Zn and Fe sulphides, Mn-Mg oxy-hydroxides and putative manganobrucite were also identified in one sample collected at an orifice vent. In this sample, micro-chimneys (conduits) composed of isocubanite and sphalerite were also identified. Mount Saldanha sediments show a clear enrichment in elements such as Mn, Mg, Fe, Cu, P and V, derived from hydrothermal fluids, and Ni, Cr and Co, derived from ultramafic rocks. The geochemical data together with the observed mineral assemblage suggest that the hydrothermal fluids are at a higher temperature than those measured at the escape orifices (7-9°C), and a strong enrichment in Mg, mainly at the top of the mount, agrees with extensive mixing of the hydrothermal fluid with unmodified seawater. Nevertheless, the mineral assemblage of MS sediments is consistent with the precipitation from hydrothermal fluids at much lower temperatures than at Rainbow. The presence of serpentinized and steatitized (talcshist) ultramafic rocks and the occurrence of a strong methane anomaly within the overlying water column collectively suggest that the hydrothermal circulation at MS is driven by exothermic reactions closely associated with the serpentinization process. Rainbow sediments have a higher concentration in transition metals and consequently an enrichment in sulphides. These differences are likely to be a consequence of the higher temperature of hydrothermal fluids, reflected in the composition of hydrothermal solutions, and of a stronger hydrothermal flux at the Rainbow site. © 2005 Elsevier B.V. All rights reserved.
Keywords: HYDROTHERMAL SEDIMENTS; LOW-TEMPERATURE VENTS; MOUNT SALDANHA HYDROTHERMAL FIELD